Academic policy for establishing new junior high schools in South Tangerang City - Mustofa Kamil; Neneng Nurjanah; Muhammad Yus Firdaus; Bambang Mardi Sentosa; Purnomo Purnomo; Cucu Sukmana (Himpunan Pengembang Kurikulum Indonesia, 2024)
This study explores the academic policy regarding establishing new Junior High Schools (SMP) in South Tangerang City in response to the rising number of Elementary School (SD) graduates and the limited availability of secondary education facilities. Using a theoretical and quantitative approach, the research applies the